O sistema agroindustrial do leite do Rio Grande do Sul e a estrutura de governança nas transações com leite em Cruz Alta - RS - Casali, Marisandra da Silva (2012)
From the 1990s the Agroindustrial Milk System in Brazil has changed because of institutional, organizational, technological, economic, and strategic questions. The relations among the system segments, especially the milk producer and the processing industry have been of different ways and there must be a greater coordination among these agents. It has occurred a n incresed demanding of producing in a higher scale, of adopting highly developed new technologies in order to achieve a better quality level and a larger regularity in ofering products. It requires a bigger investment from the rural producer in producing milk, otherwise it will be impossible todo this activity. Thus, this paper aimed to describe the Agroindustrial Milk System of Rio Grande do Sul state and to determine the predominant governance strucuture in deals between milk producers and the processing industry, under the producer s view. The theoretical fundaments used based in the analysis were de concept of Agroindustrial System and the theory of Economy of Transaction Costs. The characterization of milk SAG in Rio Grande Sul state was carried out thorugh secondary sources. IN the governance investigation, it was made a field survey with 23 rural milk producers in the municipality o Cruz Alta, in Rio Grande do Sul state. It was noticed the imprtance and the representativeness of milk SAG or the development of agrobusiness in our state. Rio Grande do Sul state is the second biggest milk producer in Brazil and the Northwest mesoregion of Rio Grande do Sul is the one which presented, from 1999 to 2009, the fastest growth in milk production, with its growth average being higher the the national one. In the Northwest mesoregion there also the highest concentration of milk producers. Over 90 of the milk taken in RS state is by means of cooperatives. In the field survey, it was found that there is a bilateral dependence between the producer and the agroindustry. Among the three governance structures defined by Williamson (1985), the most suitable for this study is the hybrid way, that is located among the governance extreme points via market and hierarchy. Although, it can be stated that it is closer to the market than to the formal contract. In the analyzed transaction features, frequency, uncertainty grade and the active specificity, it was observed that the frequency in the transactions from the studied agents is recorrent and the uncertainty is inexpressive. The specific active might be considered of low specificity. Therefore, the transaction costs are reduced for the milk and it justifies a hybrid governance structure, without any formal contract although there is a certaing degree of dependence among them. This dependence is not high enough to incentivate the contracts.